Legal Framework and Developing Part of Trade Facilitation in the Shanghai Cooperation Organization (International relations and international law Journal, 2025)
The Shanghai Cooperation Organization’s Inaugural Declaration explicitly initiated negotiations on investment facilitation, a theme consistently reaffirmed in subsequent heads of state declarations. From the perspective of organizational law, the SCO Charter advances investment facilitation, while memoranda and protocols function as soft law instruments supporting its implementation. Despite the absence of a unified definition of investment facilitation at the global level, the SCO conceptualizes it as a set of practices undertaken by member states to attract foreign investment, enhance efficiency across the investment cycle, and ensure transparency, simplified procedures, and predictability, in line with the requirements of the prospective SCO Free Trade Area. The article first analyzes the current status of the SCO, identifying four key reasons for the absence of a formal trade facilitation framework. It then examines both the contemporary context and the inherent institutional advantages for developing such a mechanism, while also exploring its normative foundations from a legal perspective. On this basis, the study proposes a prospective framework for SCO trade facilitation rules and discusses the potential for adopting a Shanghai Cooperation Organization Trade Facilitation Agreement. The article argues that the institutionalization of the facilitation under the SCO would not only stimulate economic development among member states but also contribute to the deepening of regional cooperation within the organization.Keywords: Shanghai Cooperation Organization (SCO), trade and investment facilitation, legal framework, soft law instruments, regional economic cooperation, free trade area.